A.
f(x)= 2-x
let us find f⁻¹(x)
let us say f(x)=y
y=2-x
now we switch x as y and y as x
x=2-y
solve for y
y=2-x
f⁻¹(x)=2-x
so here f(x) and f⁻¹(x) are same
B.
f(x)=-x
let us find f⁻¹(x)
let us say f(x)=y
y=-x
now we switch x as y and y as x
x=-y
solve for y
y=-x
f⁻¹(x)=-x
so here f(x) and f⁻¹(x) are same
C.
f(x)=2x
let us find f⁻¹(x)
let us say f(x)=y
y=2x
now we switch x as y and y as x
x=2y
solve for y
y=x/2
f⁻¹(x)=x/2
so here f(x) and f⁻¹(x) are not same
D.
f(x) =2/x
let us find f⁻¹(x)
let us say f(x)=y
y=2/x
now we switch x as y and y as x
x=2/y
solve for y
y=2/x
f⁻¹(x)=2/x
so here f(x) and f⁻¹(x) are same